Innovative Approaches in Pediatric Drug Formulation Catering to Specialized Need: Review Article - Mohd. Wasiullah; Piyush Yadav; Satish Kumar Yadav; Ratnesh Yadav (International Journal of Biochemistry and Biomolecule Research, 2025)
This detailed article review examines innovations in pediatric drug formulation, highlighting developments that cater to children’s specific healthcare needs. It covers pediatric pharmacology and advanced solutions like nanoparticle drug delivery and taste-making techniques, focusing on improving the safety, effectiveness, and acceptability of medications for young patients. The review highlights the benefits for patients, including improved adherence to treatment, fewer side effects, and better overall treatment outcomes. It also addresses regulatory and ethical issues, emphasizing the need for a careful balance between scientific advancements and ethical responsibilities. The conclusion envisions a future with precision medicine and personalized formulations while recognizing. The challenges ahead for pediatric healthcare. It includes novel dosage forms designed for children, like oral liquids, orally disintegrating tablets, and chewable options, as well as advancements in taste-masking technologies to improve medication palatability. The review also emphasizes age-appropriate dosing, personalized medicine strategies, and user-friendly administration devices.
Keywords: Drug Formulation; Nanoparticles; Patient Compliance; Pediatric Pharmacology; Regulatory compliance